Penerapan Manajemen Mutu Dalam Meningkatkan Kinerja Keuangan Bni Syariah Periode 2010 – 2017 - Galuh Gita Pratiwi; Nur S Buchori; Mustafa Kamal (Jurnal Ekonomi dan Perbankan Syariah, 2018)
The aims of this reasearch is to know the impact implimentation of quality management to increase BNI Syariah financial performance. The methods used to measure financial performance in this study is to compare BNI Syariah financial ratios (capital adequacy ratio, rentability ratio, and liquidity ratio). As for the collection methode in this research is used interview and BNI Syariah annual report periode 2010 untill 2017. The result of this study is quality management applied to BNI Syariah has positive impact on the capital adequacy ratio and profability, especially ROA and ROE. As for the implementation of the management quality applied BNI Syariah in accordance with the principles TQM that proclaimed by ISO, namely the customer focus, leadership, enggagement of people, processing approach, improvement, evidence based decision making, and relationship management.